Distribution of chronic wasting disease (CWD) prions in tissues from experimentally exposed coyotes (Canis latrans) - Nancy Ho; Reece McGinn; Paulina Soto; Terry R. Spraker; Justin Fischer; Kurt VerCauteren; Tracy Nichols; Rodrigo Morales (PLoS ONE, 2025)
Cervids susceptible to chronic wasting disease (CWD) are sympatric with multiple other animal species that can interact with infectious prions. Several reports have described the susceptibility of other species to CWD prions, or their potential to transport them. One of these species is the coyote (Canis latrans), which has been previously shown to pass transmission-relevant prion titers in their feces for at least three days after ingesting prion-positive brain material. The current study followed up on these findings and evaluated the distribution of prions in multiple tissues from the same coyotes. Our results show that prions persist in the digestive tract of prion-exposed coyotes five days after exposure. Moreover, prion seeding activity was identified in other tissues, including lymph nodes and lungs. These results provide additional information about the dynamics of CWD prions in the environment and show the initial fate of prions after ingestion by a canid species that is a carnivorous predator and scavenger.